2008
DOI: 10.1507/endocrj.k07e-008
|View full text |Cite
|
Sign up to set email alerts
|

Four Japanese Patients with Adrenal Hypoplasia Congenita and Hypogonadotropic Hypogonadism Caused by DAX-1 Gene Mutations: Mutant DAX-1 Failed to Repress Steroidogenic Acute Regulatory Protein (StAR) and Luteinizing Hormone .BETA.-subunit Gene Promoter Activity

Abstract: Abstract. Mutations of DSS (dosage sensitive sex reversal)-AHC critical region on the X chromosome, gene 1 DAX-1(NROB1)] results in X-linked adrenal hypoplasia congenita (AHC) and hypogonadotropic hypogonadism (HHG). Here we report four Japanese patients with AHC and HHG caused by the mutations of the DAX-1 gene. All patients manifested adrenal crisis at early childhood. Three patients did not show any pubertal sign and were diagnosed as having HHG. One patient manifested spontaneous pubertal development at 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…In this case, the GnRH and hCG tests performed showed a null responsiveness, unlike his brother. The responses observed in the two patients are consistent with the clinical manifestations, and similar than those described in the literature [12].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this case, the GnRH and hCG tests performed showed a null responsiveness, unlike his brother. The responses observed in the two patients are consistent with the clinical manifestations, and similar than those described in the literature [12].…”
Section: Discussionsupporting
confidence: 90%
“…Whilst onset of adrenal insufficiency in the neonatal period and the development of hypogonadotropic hypogonadism occur frequently [4], other less frequent clinical forms have been described, such as adrenal insufficiency appearing during infancy [5], partial forms detected in adulthood [6,7] or cases of neonatal adrenal crisis not requiring replacement treatment during a limited period of time [8]. As for hypogonadotropic hypogonadism, the failure is most often in the hypothalamic or pituitary glands or in both and the clinical spectrum is also quite varied, from complete forms of hypogonadotropic hypogonadism [9], incomplete forms [10], interrupted puberty [11,12] and precocious puberty [13]. AHC has been associated with glycerol-kinase deficit and Duchene's muscular dystrophy, when deletions occur in the region where DAX1 is located and including adjacent genes, the alteration of which causes these illnesses [14].…”
Section: Introductionmentioning
confidence: 99%
“…1) (Reutens et al, 1999, Lin et al, 2006, Achermann et al, 2000, Muscatelli et al, 1994, Zanaria et al, 1994, Guo, Mason, Stone et al, 1995, Takahashi, Shoji, Haraguchi et al, 1997, Meloni, Cao and Rosatelli, 1996, Nakae, Abe, Tajima et al, 1997, Schwartz, Blichfeldt and Muller, 1997, Peter, Viemann, Partsch et al, 1998, Seminara, Achermann, Genel et al, 1999, Bassett, O’Halloran, Williams et al, 1999, Caron, Imbeaud, Bennet et al, 1999, Merke, Tajima, Baron et al, 1999, Tabarin, Achermann, Recan et al, 2000, Domenice, Latronico, Brito et al, 2001, Wiltshire, Couper, Rodda et al, 2001, Sekiguchi, Hara, Matsuoka et al, 2007, Bernard, Ludbrook, Queipo et al, 2006, Verrijn Stuart, Ozisik, de Vroede et al, 2007, Landau, Hanukoglu, Sack et al, 2010, Li, Liu, Zhang et al, 2010, Sykiotis, Hoang, Avbelj et al, 2010, Abe, Nakae, Yasoshima et al, 1999, Achermann, Meeks and Jameson, 2001, Ahmad, Paterson, Lin et al, 2007, Argente, Ozisik, Pozo et al, 2003, Balsamo, Antelli, Baldazzi et al, 2005, Brown, Scobie, Townsend et al, 2003, Calliari, Longui, Rocha et al, 2007, Frapsauce, Ravel, Legendre et al, 2011, Garcia-Malpartida, Gomez-Balaguer, Sola-Izquierdo et al, 2009, Guo, Burris, Zhang et al, 1996, Habiby, Boepple, Nachtigall et al, 1996, Hamaguchi, Arikawa, Yasunaga et al, 1998, Kinoshita, Yoshimoto, Motomura et al, 1997, Krone, Riepe, Dorr et al, 2005, Lam, Cheng, Poon et al, 2006, Mantovani, Ozisik, Achermann et al, 2002, Mericq, Ciaccio, Marino et al, 2007, Nakae, Tajima, Kusuda et al, 1996, Ozisik, Mantovani, Achermann et al, 2003, Salvi, Gomez, Fiaux et al, 2002, Tsai and Tung, 2005, Wang, Killinger and Hegele, 1999, Wu, Zhang, Zhou et al, 2011, Yanase, Takayanagi, Oba et al, 1996, Zhang, Guo, Wagner et al, 1998, Zhang, Huang, Anyane-Yeboa et al, 2001, Franzese, Brunetti-Pierri, Spagnuolo et al, 2005, Laissue, Copelli, Bergada et al, 2006, Okuhara, Abe, Kondo et al, 2008). After other known causes (i.e., congenital adrenal hyperplasia, CAH) have been excluded, it is estimated that as many as 50% of boys with idiopathic primary adrenal insufficiency may have mutations in DAX1 (…”
Section: Human Studiesmentioning
confidence: 99%
“…To date, few biopsies of testis were performed [4, 5, 20, 21, 24]. Only the biopsy conducted by Frapsauce et al [5] revealed the presence of few spermatozoa.…”
Section: Discussionmentioning
confidence: 99%